Islamic Feminism: Gender Equity By Deconstructing Tradition - Deeba, Farah (2016)
Modernity coupled with Industrial Revolution and raising secularism paved way for a new ensemble of social unity. Individualism that penetrated the core of modern society brought many changes to the application of many pre-modern values like justice, equality and liberty. From such passage from pre-modern to modern world we witness the birth of one of the most influential movements in modern world on the level of social dynamics; Feminism. Feminism started its treatment of women under the banner of secular feminism but soon it died out because of Muslim society’s civilizational context, which was unlike Christianity. Secular feminism feed a catalyst to the contemporary Muslim woman thinkers who later on came up with the more intellectual and academic approach to secular feminism called; Islamic Feminism. Islamic Feminism maidenly raised the question on masculine interpretations of Sacred Text. Inclusion of feminine voice in reinterpretation of the Holy Scripture rendered the underlined meanings of gender which launched a potent discourse on gender equity within the Islamic framework in traditional society. The purpose of this paper is to present the contribution of Islamic Feminism in the exploration of lost reality of Islamic egalitarian society by conducting content analysis.